Measurement of fetal abdominal and subscapular subcutaneous tissue thickness during pregnancy to predict macrosomia: a pilot study. - Ling Chen; Jing-Jing Wu; Xiao-Hui Chen; Li Cao; Yun Wu; Li-Jun Zhu; Kang-Tai Lv; Chen-Bo Ji; Xi-Rong Guo (PLoS ONE)
This study assessed the growth trends and reference ranges of the ultrasound parameters, fetal abdominal subcutaneous tissue thickness (ASTT) and subscapular subcutaneous tissue thickness (SSTT), in the last two trimesters of normal pregnancy in a Chinese population. We recruited 744 healthy women with singleton pregnancies. The ASTT and SSTT were evaluated at different times between 21 and 36 weeks of gestation. The correlations between these parameters and fetal gestational weeks were assessed using linear regression analysis. Both ASTT and SSTT increased with gestation, and both parameters showed a strong correlation with gestation (ASTT vs. GA, R(2) = 0.792; P<0.0001; SSTT vs. GA, R(2) = 0.302; P<0.0001). Time-specific reference ranges, including 5th, 50th and 95th percentiles and means ± SD, were constructed for ASTT and SSTT. These results provide a preliminary reference range to evaluate whether fetal development and maternal metabolic health is normal or not in a Chinese population.